UPAYA PENINGKATAN POTENSI DIRI CREATIVE DOCTORPRENEUR DI ERA COMPETITIVE HEALTHPRENEUR BERBASIS DIGITAL MELALUI EDUKASI DAN INOVASI PLATFORM DESIGN HEALTHPRENEURSHIP - Tia Wida Ekaputri Hz; Miftahurrahmah Miftahurrahmah; Esa Indah Ayudia; Raihanah Suzan; Willi Hardy Marpaung (Universitas Jambi, 2023)
ABSTRACT In the current era of digitalization, healthpreneur products at affordable prices and good quality in the community have competitive value. Innovation in the health sector, especially to improve healthcare services, goes hand in hand with technological advances. The existence of competitive healthpreneurs motivates healthcare services to be universal and easier to access by the wider community. This community service activity aims to increase the potential of creative doctorpreneurs in the digital-based competitive healthpreneur era through education and innovative healthpreneurship design platforms. The activity was a webinar inviting resource persons in the digital-based doctorpreneur field and founders of several healthpreneurship platforms. Pretest, posttest and evaluation questionnaires were given to webinar participants. After the expert presentation, participants were allowed to discuss. Data analysis used the Wilcoxon test to determine the increase in knowledge participants. The number of webinar participants who participated was 290 students from 4 classes, namely 66 students from the Class of 2020, 99 students from the Class of 2021, 66 students from the Class of 2022 and 59 students from the Class of 2023. There was a significant difference in the pretest and posttest scores of the webinar participants. (P-value=0.008). The activity evaluation results through the webinar satisfaction questionnaire showed that most participants stated that the seminar activities were very good and good. This webinar activity is proven to increase knowledge about the potential of creative doctorpreneurs in the digital-based competitive healthpreneur era. Keywords: creative doctorpreneur, competitive healthpreneur, platform design healthpreneurship Â ABSTRAK Di era digitalisasi saat ini, produk healthpreneur dengan harga terjangkau dan berkualitas di komunitas masyarakat telah memiliki nilai kompetisi. Inovasi di bidang kesehatan khususnya dalam upaya meningkatkan healthcare service bergandengan dengan kemajuan teknologi. Dengan adanya competitive healthpreneur memotivasi healthcare service bersifat universal dan lebih mudah untuk diakses oleh masyarakat luas. Tujuan dari pelaksanaan kegiatan pengabdian kepada masyarakat ini adalah untuk meningkatkan potensi diri creative doctorpreneur di era competitive healthpreneur berbasis digital melalui edukasi dan inovasi platform design healthpreneurship. Kegiatan dilangsungkan secara webinar dengan mengundang narasumber di bidang doctorpreneur berbasis digital dan founder beberapa platform healthpreneurship. Pretest dan posttest serta kuesioner evaluasi kegiatan diberikan kepada peserta webinar. Setelah dilakukan pemaparan oleh narasumber, diberikan kesempatan untuk diskusi kepada peserta. Analisa data digunakan uji Wilcoxon untuk mengetahui peningkatan pengetahuan. Jumlah peserta webinar yang berpartisipasi sebanyak 290 mahasiswa yang berasal dari 4 angkatan, yaitu 66 orang Angkatan 2020, 99 orang Angkatan 2021, 66 orang Angkatan 2022 dan 59 orang Angkatan 2023.. Terdapat perbedaan yang signifikan nilai pre-test dan post-test peserta webinar (P-value=0,008). Hasil evaluasi kegiatan melalui kuesioner kepuasan webinar menunjukkan mayoritas peserta menyatakan kegiatan seminar sangat baik dan baik. Kegiatan webinar ini terbukti dapat meningkatkan pengetahuan tentang potensi diri creative doctorpreneur di era competitive healthpreneur berbasis digital. Kata kunci: creative doctorpreneur, competitive healthpreneur, platform design healthpreneurship